2021
DOI: 10.1108/jic-08-2020-0277
|View full text |Cite
|
Sign up to set email alerts
|

Translating green strategic intent into green process innovation performance: the role of green intellectual capital

Abstract: PurposeMany firms struggle to implement strategies that can successfully enhance the environmental sustainability of their processes. Drawing on the theories of green intellectual capital and complementary assets, this study develops a model describing the mechanism whereby firms can translate a green (i.e., environmental) strategy into a superior green process innovation performance (GPIP).Design/methodology/approachRegression analysis of multi-source survey data collected from 514 managers at 257 firms (257 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 156 publications
(229 reference statements)
4
98
1
2
Order By: Relevance
“…On the other hand, environmental consciousness pushes the leaders to create environmental policies and environmental management systems as green structural capital, consequently supporting the implementation of green activities [86]. This is consistent with Jirakraisiri and colleagues, who showed that the stronger the organizational strategic intent with whom firms make green choices, the higher the GIC reported by the managers in the environmental and safety departments [71].…”
Section: Antecedents Of Gicsupporting
confidence: 62%
See 2 more Smart Citations
“…On the other hand, environmental consciousness pushes the leaders to create environmental policies and environmental management systems as green structural capital, consequently supporting the implementation of green activities [86]. This is consistent with Jirakraisiri and colleagues, who showed that the stronger the organizational strategic intent with whom firms make green choices, the higher the GIC reported by the managers in the environmental and safety departments [71].…”
Section: Antecedents Of Gicsupporting
confidence: 62%
“…Consistently with the GIC framework, assuming its prominent role in enhancing the corporate competitive advantage, several empirical studies tested the effect of the adoption of a GIC paradigm on organizational performance outcomes. Studies that used a global measure of GIC or that did not distinguish between GIC dimensions in their statistical models (N = 8) found an association between GIC and organizational performance, measured as financial performance [57,69,70], innovation performance [71], or financial, social, and environmental performance [58]. Corporate competitive advantage emerged as an outcome of the adoption of GIC as well [6,57,72,73].…”
Section: Outcomes Of Gic (In Studies With No Distinction Among Dimensions)mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 7 shows the analysis of the moderating effect of strategic HRM involvement using logistic regression (Dawson, 2014) as used by Jirakraisiri et al (2021) in their study. The two-way interaction of logistic regression by Jeremey Dawson (2014) was used in the study.…”
Section: Assessment Of Path Modelmentioning
confidence: 99%
“…Human capital (HCI): Human capital, specifically innovative talents, is a key factor in the success of green innovation [ 63 ]. As the most dynamic element in green innovation, human capital can not only “increase marginal returns and decrease marginal costs” with investment growth but can also provide an inexhaustible impetus for this.…”
Section: Methodsmentioning
confidence: 99%